Handbook of environmental management and technology - Holmes, Gwendolyn (John Wiley & Sons, 1993)
"The past few decades have witnessed a profound awakening of popular concern with environmental issues. As a result, known sources of air, land, and water pollution are now subject to more intense scrutiny than ever before, and engineers, managers and entrepreneurs in both the public and private sectors are required to have at least a fundamental working knowledge of environmental management. Written for those with